Method for preparing polylactic acid film based on liquid substrate, polylactic acid film and application
Patent Information
- Application Number
- CN202611103219.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]针对背景技术提出的问题,本发明的目的在于提出一种基于液体基底制备聚乳酸薄膜的方法,制备得到的聚乳酸薄膜具有可降解性,成膜均匀性好,方便调控聚乳酸薄膜的微观孔隙结构和雾度,可以获得非对称孔结构的聚乳酸薄膜,解决了现有聚合物薄膜的制备方法成膜均匀性差、难以调控薄膜的微观孔隙结构和雾度的技术问题
1、采用聚乳酸-乙酸乙酯/水相的液体基底的超铺展成膜体系:采用聚乳酸作为成膜主体材料,采用乙酸乙酯作为溶剂,采用水相液体作为液体基底。乙酸乙酯能够溶解聚乳酸,同时又可与水相液体发生有限混溶。当聚乳酸成膜溶液接触液体基底的液面后,乙酸乙酯向液体基底扩散,液体基底也会影响聚乳酸成膜溶液的界面组成,导致界面区域产生表面张力梯度,进而驱动聚乳酸成膜溶液在液体基底的液面上快速铺展。与传统固体基底刮涂、旋涂或浇铸方法不同,本发明利用液体基底作为成膜支撑界面,避免了固体基底对薄膜剥离、表面缺陷和厚度不均的影响,有利于形成大面积、连续、可收集的聚乳酸薄膜。
Smart Images

Figure CN122958756A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polylactic acid (PLA) film preparation technology, and particularly to a method for preparing PLA films based on a liquid substrate, PLA films, and their applications. Background Technology
[0002] Traditional food packaging films are mostly made of petroleum-based plastics such as low-density polyethylene and polypropylene. These materials have advantages such as low cost, mature processing, and stable mechanical properties, and are therefore widely used in food packaging, fruit and vegetable preservation, and disposable packaging. However, petroleum-based plastics are difficult to degrade in the natural environment, and their disposal can easily cause white pollution and microplastic pollution.
[0003] Polylactic acid (PLA) is a typical bio-based biodegradable polymer material. Due to its good transparency, biocompatibility, and processability, it has been widely used in food packaging, fruit and vegetable preservation, and disposable packaging materials. Compared with traditional petroleum-based packaging materials such as polyethylene and polypropylene, PLA has significant application potential in green and biodegradable packaging. Existing research typically improves the packaging performance of PLA through blending (such as melt blending), composite fillers (composite modification), plasticization, introduction of antimicrobial components, or multilayer structural design.
[0004] Currently, common methods for preparing polymer films mainly include melt extrusion, casting, solution casting, blade coating, spin coating, and roll-to-roll coating. While these methods can prepare polylactic acid (PLA) films, they still have the following problems: Melt extrusion and casting are suitable for industrial production, but they usually require high-temperature processing equipment, and the resulting films are often relatively dense; solution casting and blade coating are simple to operate, but they typically rely on a solid substrate, and the film formation process is easily affected by solvent evaporation rate, substrate wettability, liquid film thickness, and environmental conditions. The film drying time is relatively long, and the film uniformity and micropore structure control capabilities are limited.
[0005] For food preservation packaging, a denser film is not necessarily better. High-fat or highly oxidizing foods typically require strong oxygen and moisture barrier properties, while fresh produce such as fruits and vegetables continue to respire after harvest, necessitating a balance between water retention and gas exchange in the film. Improving the performance of existing PLA preservation films usually requires the addition of additional polymer components or composite additives, and the preparation process mainly relies on melt blending or conventional film-forming methods, making it difficult to directly control the micron-level pore structure and haze of the film. Summary of the Invention
[0006] In response to the problems raised in the background art, the purpose of this invention is to propose a method for preparing polylactic acid (PLA) films based on a liquid substrate. The prepared PLA films are biodegradable, have good film uniformity, and allow for easy control of the micropore structure and haze of the PLA films. Asymmetric pore structures of PLA films can be obtained, thus solving the technical problems of poor film uniformity and difficulty in controlling the micropore structure and haze of existing polymer film preparation methods.
[0007] Another objective of this invention is to propose that the polylactic acid film prepared by the above method is biodegradable, has uniform film thickness, and adjustable micropore structure and haze.
[0008] Another object of the present invention is to propose the application of the above-mentioned polylactic acid film in food packaging.
[0009] The above-mentioned technical objective of the present invention is achieved through the following technical solution: A method for preparing polylactic acid films based on a liquid substrate includes the following steps: Step S1: Prepare polylactic acid film-forming solution: Add polylactic acid to ethyl acetate and stir to dissolve, thus obtaining polylactic acid film-forming solution; Step S2: Prepare the liquid substrate: Add the aqueous liquid to a container to obtain the liquid substrate, and perform temperature control treatment on the liquid substrate; Step S3: Add the polylactic acid film-forming solution into the injection tool, so that the liquid outlet of the injection tool contacts the liquid surface of the liquid substrate, so as to apply the polylactic acid film-forming solution to the liquid surface of the liquid substrate. After the polylactic acid film-forming solution contacts the liquid surface of the liquid substrate, it spreads on the liquid surface to form a thin film. Step S4: After the film formed in step S3 has been allowed to stand, the film is collected from the surface of the liquid substrate and dried to obtain a polylactic acid film. The temperature of the liquid substrate is adjusted to regulate the pore structure and haze of the polylactic acid film.
[0010] Optionally, the temperature of the liquid substrate is 0–50°C.
[0011] Optionally, in step S1, the polylactic acid is selected from one or more of low-melting-point polylactic acid, high-melting-point polylactic acid, polylactic acid homopolymer, polylactic acid copolymer and modified polylactic acid; The polylactic acid film-forming solution contains 5–20 wt% polylactic acid.
[0012] Optionally, the polylactic acid in the polylactic acid film-forming solution has a mass fraction of 11-15 wt%.
[0013] Optionally, the aqueous phase liquid is water or deionized water; The liquid level of the liquid substrate is 2 to 8 cm.
[0014] Optionally, in step S3, the applied volume of the polylactic acid film-forming solution is 15 μL to 20 mL, and the supply rate of the polylactic acid film-forming solution is 0.1 to 10 mL / min.
[0015] Optionally, in step S4, the standing time of the film is 0.5 to 30 minutes, and the drying conditions are drying at 30 to 50 °C for 10 to 60 minutes.
[0016] Optionally, the polylactic acid film obtained after drying in step S4 has a thickness of 0.05–100 μm and a haze of 3–95%.
[0017] A polylactic acid film is prepared using the aforementioned method for preparing polylactic acid films based on a liquid substrate.
[0018] The application of the polylactic acid film in food packaging.
[0019] Compared with the prior art, the embodiments of the present invention have the following beneficial effects: 1. A superspreading film-forming system using a polylactic acid-ethyl acetate / aqueous liquid substrate: Polylactic acid (PLA) is used as the main film-forming material, ethyl acetate as the solvent, and an aqueous liquid as the liquid substrate. Ethyl acetate can dissolve PLA and is also partially miscible with the aqueous liquid. When the PLA film-forming solution comes into contact with the surface of the liquid substrate, ethyl acetate diffuses into the liquid substrate, and the liquid substrate also affects the interfacial composition of the PLA film-forming solution, resulting in a surface tension gradient in the interfacial region, which in turn drives the PLA film-forming solution to spread rapidly on the surface of the liquid substrate. Unlike traditional solid substrate coating, spin coating, or casting methods, this invention uses the liquid substrate as the film-forming support interface, avoiding the influence of the solid substrate on film peeling, surface defects, and uneven thickness, which is beneficial for forming large-area, continuous, and collectable PLA films.
[0020] 2. Application method using the liquid outlet of the injection tool to contact the liquid surface of the liquid substrate: This method does not involve directly dripping the polylactic acid film-forming solution from above the liquid substrate, nor does it involve inserting the liquid outlet of the injection tool below the liquid surface of the liquid substrate. Instead, it involves contacting the liquid outlet of the injection tool with the liquid surface of the liquid substrate, allowing the polylactic acid film-forming solution to smoothly enter the liquid surface of the liquid substrate and form a thin film. This results in a more uniform film formation and less loss of the polylactic acid film-forming solution.
[0021] 3. By controlling the temperature of the liquid substrate, the pore structure and haze of polylactic acid (PLA) films can be adjusted to obtain transparent and dense PLA films and hazy, porous PLA films. A low-temperature liquid substrate slows down the evaporation and diffusion rate of ethyl acetate, prolonging phase separation time and creating numerous micron-sized pores in the PLA matrix, resulting in a hazy, porous PLA film. A liquid substrate at room temperature or higher allows for faster solvent evaporation and diffusion, leading to rapid PLA solidification and the formation of a relatively dense, transparent, and low-haze PLA film. The same PLA-ethyl acetate system can be used to prepare two types of products—transparent and dense PLA films and hazy, porous PLA films—by adjusting the temperature of the liquid substrate, avoiding the need to modify the formulation or add pore-forming agents to alter the film structure in traditional processes. By adjusting the temperature of the liquid substrate, transparent, semi-transparent, or high-haze porous PLA films can be obtained without introducing additional foaming agents, inorganic fillers, or complex modifiers.
[0022] 4. This method can obtain asymmetric Janus polylactic acid (PLA) films with tunable pore structures: PLA films prepared using this method can have asymmetric structures with different pore structures on both sides, i.e., Janus films. Due to the different rates of solvent evaporation, diffusion, cooling, and phase separation on the side of the film near the air and the side near the liquid substrate, the pore size, pore density, or pore area ratio on both sides can differ. One side can be porous, while the other side can be relatively dense; or both sides can have pore structures but with different pore sizes and densities. The low temperature conditions of the liquid substrate further amplify this difference, with a more pronounced microporous structure forming on the side near the aqueous phase, while the side near the air is relatively dense or has fewer pores, thus forming an asymmetric Janus structure. This asymmetric structure is of great significance in applications where the two sides of the film need to perform different functions. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of a method for preparing polylactic acid films based on a liquid substrate according to an embodiment of the present invention.
[0024] Figure 2 These are actual product images of the polylactic acid films from Examples 6, 7, and 8 of this invention. Figure 2 Image (a) is a photograph of the finished polylactic acid film from Example 6. Figure 2 Image (b) is a photograph of the finished polylactic acid film from Example 7. Figure 2 (c) is a physical image of the polylactic acid film product of Example 8.
[0025] Figure 3 These are actual product images of the polylactic acid films from Examples 1, 2, and 3 of this invention. Figure 3 Image (a) is a photograph of the finished polylactic acid film from Example 1. Figure 3 Image (b) is a photograph of the finished polylactic acid film from Example 2. Figure 3 (c) is a physical image of the polylactic acid film product of Example 3.
[0026] Figure 4 These are SEM images of the polylactic acid films from Examples 8, 4, 5, 6, and 7, showing the air side (air side) and the liquid side (water side) near the liquid substrate. Figure 4 Image (a) is a SEM image of the air side of the polylactic acid film in Example 6. Figure 4 Image (b) is a SEM image of the water side of the polylactic acid film in Example 6. Figure 4 Image (c) is a SEM image of the air side of the polylactic acid film in Example 7. Figure 4 Image (d) in the image is a SEM image of the water side of the polylactic acid film in Example 7. Figure 4 Image (e) in the image is a SEM image of the air side of the polylactic acid film in Example 8. Figure 4 Image (f) is a SEM image of the water side of the polylactic acid film in Example 8. Figure 4 (g) is a SEM image of the air side of the polylactic acid film in Example 4. Figure 4 (h) is the SEM image of the polylactic acid film on the water side of Example 4. Figure 4 Image (i) is a SEM image of the air side of the polylactic acid film in Example 5. Figure 4 (j) is the SEM image of the water side of the polylactic acid film in Example 5.
[0027] Figure 5 These are macroscopic haze test diagrams from Examples 1 and 2. Figure 5 (a) in the figure is a macroscopic haze test diagram of the polylactic acid film of Example 2. Figure 5 (b) is a macroscopic haze test diagram of the polylactic acid film of Example 1.
[0028] Figure 6 These are the transmittance and haze spectra of the polylactic acid films from Examples 1, 2, and 3. Figure 6 (a) in the figure is the transmittance spectrum of the polylactic acid film of Example 1. Figure 6 (b) in the figure is the haze spectrum of the polylactic acid film of Example 1. Figure 6 (c) in the figure is the transmittance spectrum of the polylactic acid film of Example 2. Figure 6 (d) in the figure is the haze spectrum of the polylactic acid film of Example 2. Figure 6 In Figure (e), the transmittance spectrum of the polylactic acid film of Example 3 is shown. Figure 6 (f) in the figure is the haze spectrum of the polylactic acid film of Example 3.
[0029] Figure 7 These are optical microscope images (500× magnification) of the air and water sides of the polylactic acid films of Examples 1, 2 and 3. Figure 7 Image (a) is an optical microscope image of the air side of the polylactic acid film in Example 1. Figure 7 Image (b) is an optical microscope image of the polylactic acid film on the water side of Example 1. Figure 7 Image (c) is an optical microscope image of the air side of the polylactic acid film in Example 2. Figure 7 Image (d) in the image is an optical microscope image of the polylactic acid film on the water side of Example 2. Figure 7 Image (e) in the figure is an optical microscope image of the air side of the polylactic acid film in Example 3. Figure 7 (f) is an optical microscope image of the water side of the polylactic acid film in Example 3.
[0030] Figure 8 These are SEM images of the polylactic acid films on the air and water sides of Examples 1, 2, and 3. Figure 8 Image (a) is a SEM image of the air side of the polylactic acid film in Example 1. Figure 8 Image (b) is a SEM image of the water side of the polylactic acid film in Example 1. Figure 8 Image (c) in the image is a SEM image of the air side of the polylactic acid film in Example 2. Figure 8 Image (d) in the image is a SEM image of the water side of the polylactic acid film in Example 2. Figure 8 Image (e) in the image is a SEM image of the air side of the polylactic acid film in Example 3. Figure 8 (f) is a SEM image of the water side of the polylactic acid film in Example 3.
[0031] Figure 9 This is a pore size distribution diagram of the polylactic acid film on the water side of Example 1.
[0032] Figure 10 These are the stress-strain curves of the polylactic acid films obtained in Examples 8, 4, and 5.
[0033] Figure 11 These are photographs taken during a preservation test using the polylactic acid film from Example 2. Figure 11 Image (a) in the image is taken on the first day of the test. Figure 11 Image (b) is a photo taken on the 4th day of the test. Figure 11 Image (c) in the image is taken on the 9th day of the test. Figure 11 Image (d) in the image is taken on the 13th day of the test. Figure 11 Image (e) in the image is taken on the 18th day of the test. Figure 11 (f) is a photograph taken on the 18th day after the film was removed during the test.
[0034] Figure 12These are the XRD characterization results of Examples 1 and 2.
[0035] Figure 13 These are the DSC characterization results for Examples 1 and 2. Detailed Implementation
[0036] A method for preparing polylactic acid films based on a liquid substrate includes the following steps: Step S1: Prepare polylactic acid film-forming solution: Add polylactic acid to ethyl acetate (EA) and stir to dissolve to obtain polylactic acid film-forming solution; Step S2: Prepare the liquid substrate: Add the aqueous liquid to a container to obtain the liquid substrate, and perform temperature control treatment on the liquid substrate; Step S3: Add the polylactic acid film-forming solution into the injection tool, so that the liquid outlet of the injection tool contacts the liquid surface of the liquid substrate, so as to apply the polylactic acid film-forming solution to the liquid surface of the liquid substrate. After the polylactic acid film-forming solution contacts the liquid surface of the liquid substrate, it spreads on the liquid surface to form a thin film. Step S4: After the film formed in step S3 has been allowed to stand, the film is collected from the surface of the liquid substrate and dried to obtain a polylactic acid film. The temperature of the liquid substrate is adjusted to regulate the pore structure and haze of the polylactic acid film.
[0037] A polylactic acid (PLA) film-forming solution is formed by dissolving PLA in ethyl acetate (an organic solvent with limited miscibility with water). This PLA film-forming solution is then applied to the surface of an aqueous liquid substrate via the dispensing end of a dispensing tool, allowing for contact between the dispensing end and the liquid surface. Utilizing the surface tension difference at the liquid-liquid interface, solvent exchange, and phase separation, the PLA film-forming solution rapidly superspreads on the liquid substrate surface and solidifies into a film through phase separation. Furthermore, by controlling the temperature of the liquid substrate, the pore structure and haze of the PLA film can be controlled. The characteristics of this method are as follows: 1. Superspreading film-forming system using polylactic acid-ethyl acetate / aqueous liquid substrate: Polylactic acid (PLA) is used as the main film-forming material, ethyl acetate as the solvent, and an aqueous liquid as the liquid substrate. Ethyl acetate can dissolve PLA and is also partially miscible with the aqueous liquid. When the PLA film-forming solution comes into contact with the surface of the liquid substrate, ethyl acetate diffuses into the liquid substrate. The liquid substrate also affects the interfacial composition of the PLA film-forming solution, resulting in a surface tension gradient in the interfacial region, which in turn drives the PLA film-forming solution to spread rapidly on the surface of the liquid substrate.
[0038] Unlike traditional solid substrate coating, spin coating, or casting methods, this invention uses a liquid substrate as a film-forming support interface, avoiding the influence of solid substrates on film peeling, surface defects, and uneven thickness, which is beneficial for forming large-area, continuous, and collectable polylactic acid films.
[0039] 2. Application method using the liquid outlet of the injection tool to contact the liquid surface of the liquid substrate: This method does not involve directly dripping the polylactic acid film-forming solution from above the liquid substrate, nor does it involve inserting the liquid outlet of the injection tool below the liquid surface of the liquid substrate. Instead, it involves contacting the liquid outlet of the injection tool with the liquid surface of the liquid substrate, allowing the polylactic acid film-forming solution to smoothly enter the liquid surface of the liquid substrate and form a thin film. This results in a more uniform film formation and less loss of the polylactic acid film-forming solution.
[0040] 3. By controlling the temperature of the liquid substrate, the pore structure and haze of polylactic acid (PLA) films can be adjusted to obtain transparent and dense PLA films and hazy, porous PLA films. A low-temperature liquid substrate slows down the evaporation and diffusion rate of ethyl acetate, prolonging phase separation time and creating numerous micron-sized pores in the PLA matrix, resulting in a hazy, porous PLA film. A liquid substrate at room temperature or higher allows for faster solvent evaporation and diffusion, leading to rapid PLA solidification and the formation of a relatively dense, transparent, and low-haze PLA film. The same PLA-ethyl acetate system can be used to prepare two types of products—transparent and dense PLA films and hazy, porous PLA films—by adjusting the temperature of the liquid substrate, avoiding the need to modify the formulation or add pore-forming agents to alter the film structure in traditional processes. By adjusting the temperature of the liquid substrate, transparent, semi-transparent, or high-haze porous PLA films can be obtained without introducing additional foaming agents, inorganic fillers, or complex modifiers.
[0041] 4. This method can obtain asymmetric Janus polylactic acid (PLA) films with tunable pore structures: PLA films prepared using this method can have asymmetric structures with different pore structures on both sides, i.e., Janus films. Due to the different rates of solvent evaporation, diffusion, cooling, and phase separation on the side of the film near the air and the side near the liquid substrate, the pore size, pore density, or pore area ratio on both sides can differ. One side can be a porous structure, while the other side can be a relatively dense structure; or both sides can have pore structures but with different pore sizes and densities.
[0042] The low-temperature conditions of the liquid substrate further amplify this difference, resulting in a more pronounced microporous structure on the side closer to the aqueous phase and a relatively dense or less porous structure on the side closer to the air, thus forming an asymmetric Janus structure. Since the polylactic acid (PLA) film-forming solution spreads on the surface of the liquid substrate, the upper and lower sides of the film are in completely different mass transfer environments. The liquid surface side of the liquid substrate is in direct contact with the aqueous phase, which is a strong non-solvent for PLA; ethyl acetate, on the other hand, exhibits limited miscibility with the aqueous phase. Therefore, two processes occur simultaneously on the liquid surface side of the liquid substrate: EA diffuses into the aqueous phase, and the aqueous phase enters the film in the opposite direction. This process rapidly reduces the local solubility of PLA, making non-solvent-induced phase separation (NIPS) more likely to occur near the aqueous phase interface. After phase separation, a PLA-enriched phase and an EA / water-enriched phase are formed; the former solidifies into a framework, while the latter leaves pores after subsequent diffusion, evaporation, and drying. Therefore, continuous micropores or high-pore-density regions are more likely to appear on the aqueous phase side. The dominant processes on the air side differ; ethyl acetate volatilization is the primary event, while direct entry of the aqueous phase is relatively weak. EA volatilization causes a rapid increase in PLA concentration on the air side, easily leading to the formation of a polymer-enriched "skin" or a denser surface. This densification process limits the continued growth of pores during subsequent phase separation, so the air side is more likely to exhibit a relatively smooth, dense surface with fewer pores.
[0043] This asymmetric structure is significant in applications where the two sides of the film need to perform different functions. For example, in fruit and vegetable preservation packaging, the relatively porous side can face the fruit or vegetable or the inside of the packaging, allowing for some gas exchange and moisture buffering capacity; the relatively dense side can face the external environment to reduce the entry of external pollutants and, to some extent, reduce excessive moisture loss, thus balancing the respiration and water retention needs of the fruit and vegetable. For packaging scenarios involving fresh fruits and vegetables, chilled foods, and agricultural products prone to water loss, if the film is completely dense, it may hinder gas exchange inside the packaging; if both sides of the film are highly porous, it may lead to excessive moisture loss or a decrease in mechanical integrity. Therefore, Janus membranes, with one porous side and one relatively dense side, are beneficial for achieving a balance between air permeability, water retention, and operational stability.
[0044] Furthermore, this Janus structure can also be used in biodegradable packaging materials that require unilateral light scattering or unilateral contact functionality. For example, the porous side can enhance light scattering and provide a frosted white appearance, suitable for light-shielding packaging, privacy packaging, decorative packaging, or anti-glare films; the relatively dense side can improve surface integrity and transferability, facilitating film adhesion, overlay, or lamination with other substrates.
[0045] In summary, the polylactic acid (PLA) films prepared by the method based on liquid substrates described above are biodegradable, have good film uniformity, and allow for easy control of the micropore structure and haze of the PLA films. They can also obtain PLA films with asymmetric pore structures, thus solving the technical problems of poor film uniformity and difficulty in controlling the micropore structure and haze of existing polymer film preparation methods.
[0046] To further clarify, the temperature of the liquid substrate is 0–50°C.
[0047] Specifically, the temperature of the liquid substrate can be adjusted and controlled by an ice bath, a constant temperature water bath, room temperature environment, or a heating device.
[0048] When the temperature of the liquid substrate is in the range of 0°C to less than 15°C, preferably 0–10°C, the prepared polylactic acid film has high pore density and high haze (porous, high haze, milky white or translucent polylactic acid film). When the temperature of the liquid substrate is 15–50°C, the prepared polylactic acid film has high total transmittance and low haze (low haze, highly transparent dense polylactic acid film). Preferably, when the target film is a transparent dense polylactic acid film, the temperature of the liquid substrate is preferably 20–40°C.
[0049] Furthermore, at low temperatures, the difference in surface pore structure between the air side and the liquid surface side of the asymmetric Janus polylactic acid film during preparation is amplified. At 0 ℃, the aqueous liquid substrate reduces the evaporation and diffusion rate of EA, lengthens the phase separation time window, and allows for more sufficient NIPS on the liquid surface side of the liquid substrate. Therefore, the micropores on the liquid surface side of the film are more pronounced. At 25 ℃ or 35 ℃, EA evaporates and the polymer solidifies faster, the micropore structure decreases, and the film tends to be more transparent and has a low haze.
[0050] Preferably, in step S1, the polylactic acid is selected from one or more of low-melting-point polylactic acid, high-melting-point polylactic acid, polylactic acid homopolymer, polylactic acid copolymer and modified polylactic acid; The polylactic acid film-forming solution contains 5–20 wt% polylactic acid.
[0051] The polylactic acid (PLA) is preferably a PLA material that can dissolve in ethyl acetate and form a continuous film on an aqueous liquid substrate. In a preferred embodiment, low-melting-point PLA that can form a homogeneous and transparent solution in ethyl acetate and form a continuous self-supporting film on an aqueous substrate is selected as the film-forming host material. Ethyl acetate is an organic solvent capable of dissolving PLA and exhibiting limited miscibility or interfacial mass transfer with the aqueous phase.
[0052] The method can also control the film spreading area, thickness, pore structure, and mechanical properties by adjusting the PLA concentration in the polylactic acid (PLA) film-forming solution. The inventors discovered that the mass fraction of PLA in the PLA film-forming solution (PLA concentration) affects solution viscosity, interfacial spreading ability, and phase separation structure. When the PLA concentration is too low, the solution viscosity is low, resulting in a large spreading area, but the film may exhibit localized thinness, thickness fluctuations, or insufficient mechanical strength. When the PLA concentration is too high, polymer chain entanglement is enhanced, improving skeleton continuity and mechanical properties, but the increased solution viscosity inhibits spreading, leading to localized unevenness or decreased film continuity. Therefore, this invention controls the mass fraction of PLA in the PLA film-forming solution to be 5–20 wt%.
[0053] Preferably, the polylactic acid in the polylactic acid film-forming solution has a mass fraction of 8–18 wt%.
[0054] More preferably, the polylactic acid in the polylactic acid film-forming solution has a mass fraction of 11 to 15 wt%.
[0055] Continuous films can be obtained when the mass fraction of polylactic acid in the polylactic acid film-forming solution is 11-15 wt%, and the haze, pore size, pore area ratio and mechanical properties of the film can be adjusted by the polylactic acid concentration.
[0056] In the embodiments of the present invention, polylactic acid film-forming solutions with polylactic acid concentrations of 11 wt%, 12 wt%, and 13 wt% can all form continuous films on an aqueous liquid substrate at 0 °C. As the concentration increases from 13 wt% to 15 wt%, the tensile strength and elongation at break of the polylactic acid film both increase with increasing concentration, indicating that concentration control can improve the load-bearing capacity of the polymer skeleton.
[0057] In a preferred embodiment of the present invention, the mass fraction of polylactic acid in the polylactic acid film-forming solution is 13 wt%, 14 wt%, or 15 wt%.
[0058] In this way, the structure and performance of the film can be adjusted by a single film-forming substrate concentration, without the need to add plasticizers, fillers or crosslinking components.
[0059] To further clarify, the aqueous phase liquid is water or deionized water; The liquid level of the liquid substrate is 2 to 8 cm.
[0060] The aqueous liquid is added to a container to form a stable liquid surface, resulting in a liquid substrate. The liquid surface height of the liquid substrate is 2-8 cm, which facilitates the formation of a stable liquid surface and makes it easier for the film to spread and be collected. When the liquid surface height is too low, the heat capacity of the liquid substrate is small, the temperature stability is poor, and the liquid surface is easily affected by disturbances at the bottom and boundary of the container. When the liquid surface height is too high, the improvement on the film formation effect is limited, and it is actually not conducive to temperature control, observation, and film collection.
[0061] More preferably, the liquid level of the liquid substrate is 3 to 5 cm.
[0062] It should be noted that, without compromising the superspreading and phase separation film formation of the polylactic acid film-forming solution, the aqueous phase liquid can also be an aqueous phase liquid containing a small amount of water-soluble components (e.g., salt, alcohol, glycerol, surface tension modifier, etc.).
[0063] Preferably, in step S3, the applied volume of the polylactic acid film-forming solution is 15 μL to 20 mL, and the supply rate of the polylactic acid film-forming solution is 0.1 to 10 mL / min.
[0064] Specifically, the polylactic acid (PLA) film-forming solution is loaded into an injection tool (syringe, pipette, dropper, metering pump, or continuous supply device), ensuring that the outlet of the injection tool is in tangential contact with the liquid surface of the liquid substrate. The PLA film-forming solution is applied at a uniform rate, maintaining a stable liquid surface and avoiding airflow, vibration, or mechanical disturbance. Upon contact with the liquid substrate, the PLA film-forming solution rapidly spreads under the influence of interfacial tension difference and the Marangoni effect, forming a PLA liquid film.
[0065] Preferably, in step S3, the liquid supply rate when applying the polylactic acid film-forming solution is 1 to 3 mL / min.
[0066] Preferably, in step S4, the standing time of the film is 0.5 to 30 minutes, and the drying conditions are drying at 30 to 50 °C for 10 to 60 minutes.
[0067] In step S4, after the polylactic acid film-forming solution is spread, it is allowed to stand for 0.5–30 min to allow ethyl acetate to diffuse into the aqueous liquid substrate and evaporate into the air, while simultaneously inducing phase separation and solidification of the polylactic acid into a film. Under low-temperature conditions, the evaporation and diffusion rates of ethyl acetate decrease, the phase separation process is prolonged, and the polymer-depleted phase forms a porous precursor, ultimately resulting in a porous structure. At room temperature or higher temperatures, ethyl acetate rapidly evaporates and diffuses, and the polylactic acid rapidly solidifies, forming a relatively dense structure.
[0068] Preferably, in step S4, the standing time of the film is 2 to 10 minutes.
[0069] To further illustrate, the film can be collected from the surface of a liquid substrate using tweezers, a petri dish, a collection frame, a target substrate, a roller, or a continuous substrate conveyor. The resulting film can be directly peeled off from the liquid substrate surface or transferred to PET, glass, paper, metal mesh, fabric, non-woven fabric, biodegradable substrate, or food surface. After collecting the film, it can be washed 1–5 times with deionized water to remove residual solvents and water-soluble impurities, and then dried at 30–50 °C for 10–60 min to obtain a polylactic acid film, which has the advantage of short drying time.
[0070] To elaborate further, such as Figure 1 As shown, when preparing a large-area film using the method of this invention, a portion of the polylactic acid (PLA) film-forming solution can be first applied to the liquid surface of the liquid substrate to form a primary film. After the primary film is formed and stabilized, the remaining PLA film-forming solution is applied. The subsequently applied PLA film-forming solution is received by the primary film and temporarily separated from the liquid surface of the liquid substrate, forming an interface structure of "liquid substrate-primary film-PLA film-forming solution". Subsequently, the primary film is oriented and scrubbed or pulled using clean tweezers or other scribing tools (such as needle tools, blades, traction frames, or rollers), causing the received PLA film-forming solution to re-contact the surface of the liquid substrate and rapidly spread along a predetermined direction under the traction action, ultimately forming a complete and continuous large-area film.
[0071] The method of applying the liquid by having the liquid outlet of the injection tool in contact with the liquid surface of the liquid substrate results in more uniform film formation and less solution loss. Furthermore, the film formation process using primary film receiving and directional scribing can produce films with larger areas, making it suitable for scaling up to continuous or semi-continuous film formation processes.
[0072] It should be noted that during the primary film spreading process, the primary film will stack up, so this portion of the final polylactic acid (PLA) film must be discarded. The resulting film includes the main film area formed by the secondary spreading and the edge transition film area (the transition region between the primary film and the main film area formed by the secondary spreading). In actual use, the main film area is preferred as the effective film. The edge transition film area can be removed for subsequent testing and use. To ensure the uniformity of the final PLA film (thickness), the spreading tool should be moved quickly along the liquid surface during operation, avoiding upward pulling of the film.
[0073] Preferably, during low-temperature film formation, floating ice, confinement frames, and annular baffles can be used to define the film formation area to reduce liquid film edge shrinkage and liquid surface disturbance.
[0074] To further explain, the polylactic acid film obtained after drying in step S4 has a thickness of 0.05–100 μm and a haze of 3–95%.
[0075] The polylactic acid (PLA) film prepared by the method can be a transparent and dense film, a translucent film, or a hazy, porous, asymmetric Janus film. The final thickness of the PLA film after static curing and drying is 0.05–100 μm, preferably 1–30 μm, and more preferably 2–20 μm. The haze of the PLA film is 3–95%, which can be adjusted by the liquid substrate temperature, PLA concentration, applied volume of the PLA film-forming solution, standing time, and drying conditions.
[0076] Furthermore, when the prepared polylactic acid film is a porous polylactic acid film, the average pore size of the porous polylactic acid film is 0.1 to 10 μm, preferably 0.3 to 5 μm, and more preferably 0.3 to 3.5 μm.
[0077] Furthermore, when the prepared polylactic acid film is an asymmetric Janus film, the transmittance (including total transmittance and diffuse transmittance) of the polylactic acid film on the side closer to the air is different from the transmittance on the side closer to the liquid surface of the liquid substrate.
[0078] A polylactic acid film is prepared using the aforementioned method for preparing polylactic acid films based on a liquid substrate.
[0079] The polylactic acid film prepared by the method is biodegradable, has uniform film thickness, and its micropore structure and haze are adjustable.
[0080] The application of the polylactic acid film in food packaging, especially in fruit and vegetable preservation packaging.
[0081] The polylactic acid film obtained by this invention has a biodegradable and controllable microporous structure. This microporous structure can, to a certain extent, balance water vapor barrier and gas exchange requirements, reducing moisture loss from fruits and vegetables while avoiding anaerobic respiration problems caused by complete sealing. Therefore, this film can be used for preservation packaging of fresh agricultural products such as fruits and vegetables.
[0082] To facilitate understanding of the present invention, a more complete description is provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0083] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0084] Example 1 A method for preparing polylactic acid films based on a liquid substrate includes the following steps: Step S1: Preparation of polylactic acid film-forming solution: Add 1.3g of polylactic acid (using low-melting-point polylactic acid, purity >99%, from Kobin Trading Co., Ltd.) to 8.7g of ethyl acetate (purity >99%, from Macklin), and dissolve by magnetic stirring at 60°C for 45min to obtain the polylactic acid film-forming solution. The mass fraction of polylactic acid in the polylactic acid film-forming solution is 13wt%. Step S2: Prepare the liquid substrate: Take a clean glass container and add the aqueous liquid, which is deionized water, into the container to obtain the liquid substrate. The liquid level of the liquid substrate is 4 cm. Perform temperature control treatment on the liquid substrate by placing it in an ice bath to stabilize the water temperature at 0 ℃. Step S3: Use a pipette to draw 800 μL of polylactic acid film-forming solution, keeping the dispensing end of the pipette in tangential contact with the liquid surface of the liquid substrate, and apply the polylactic acid film-forming solution to the liquid surface of the liquid substrate at a uniform speed. After the polylactic acid film-forming solution contacts the liquid surface of the liquid substrate, it quickly spreads and forms a thin film. The supply rate of the polylactic acid film-forming solution is 2 mL / min. Step S4: After the film formed in step S3 has been left to stand for 2 minutes, the film is collected from the surface of the liquid substrate with tweezers, washed with deionized water 3 times, and dried at 40°C for 20 minutes to obtain a polylactic acid film.
[0085] In Example 1, the pore structure and haze of the polylactic acid film were controlled by adjusting the temperature of the liquid substrate, resulting in a high-haze porous film.
[0086] After multi-point thickness measurement, the average thickness of the polylactic acid film obtained in Example 1 was 14.73 μm.
[0087] The polylactic acid film obtained in Example 1 is a semi-permeable membrane. Testing showed that the haze of the polylactic acid film of Example 1 was approximately 84.10% on the air side and 83.85% on the liquid side (water side) near the liquid substrate. Figure 7 (a), (b) and Figure 8 As shown in (a) and (b), uniform micropores exist on the surface of the low-temperature sample, such as Figure 9 As shown, in Example 1, the average pore size of the polylactic acid (PLA) film on the water side is approximately 1.9 μm, with the pore size concentrated between 1.5 and 2 μm. Example 1 illustrates that a low-temperature liquid substrate can induce the formation of a porous, high-haze structure in the PLA film.
[0088] Example 2 Compared with Example 1, the difference in Example 2 is that the temperature of the liquid substrate is controlled at 25 °C, while the other steps are the same.
[0089] In Example 2, the 800 μL polylactic acid film-forming solution exhibited good film-forming continuity. The resulting polylactic acid film had high transparency, with a haze of approximately 6.12%. Figure 7 (c), (d) and Figure 8 As shown in (c) and (d), observations using an optical microscope and SEM revealed that the polylactic acid film prepared at 25°C had an indistinct or virtually poreless pore structure, and was more closely resembling a dense and transparent film.
[0090] After multi-point thickness measurement, the average thickness of the polylactic acid film obtained in Example 2 was 7.78 μm.
[0091] Example 2 illustrates that ethyl acetate evaporates and diffuses rapidly on a room-temperature liquid substrate, while polylactic acid solidifies quickly, inhibiting sufficient phase separation. Therefore, a transparent, low-haze film can be prepared.
[0092] Example 3 Compared with Example 1, the difference in Example 3 is that the temperature of the liquid substrate is controlled at 35 °C, while the other steps are the same.
[0093] In Example 3, the polylactic acid film obtained from 800 μL of polylactic acid film-forming solution had a haze of approximately 5.55%, exhibiting high transparency. Figure 7 (e), (f) and Figure 8 As shown in (e) and (f), compared with the polylactic acid film prepared in Example 1, the polylactic acid film in Example 3 has significantly fewer micropores; compared with the polylactic acid film prepared in Example 2, the solvent evaporates faster at 35 °C in Example 3, and local surface micro-defects or needle-like morphology appear, so the film continuity is slightly lower than that in Example 2.
[0094] After multi-point thickness measurement, the average thickness of the polylactic acid film obtained in Example 3 was 4.78 μm.
[0095] Example 3 illustrates that an aqueous liquid substrate at 30–40 °C can be used to prepare transparent or low-haze polylactic acid films. However, when the temperature is too high, it is necessary to control the evaporation rate and liquid surface disturbance to avoid local defects.
[0096] Example 4 Compared with Example 1, the difference in Example 4 is that the mass fraction of polylactic acid in the polylactic acid film-forming solution is 14wt%, the solution volume is 1000μL, and the other steps are the same.
[0097] Example 5 Compared with Example 1, the difference in Example 5 is that the mass fraction of polylactic acid in the polylactic acid film-forming solution is 15wt%, the solution volume is 1000μL, and the other steps are the same.
[0098] Multi-point thickness measurements showed that the average thickness of the polylactic acid (PLA) film obtained in Example 4 was 4.40 μm, the tensile strength was 22 MPa, and the elongation at break was 34%. Multi-point thickness measurements also showed that the average thickness of the PLA film obtained in Example 5 was 8.00 μm, the tensile strength was 24 MPa, and the elongation at break was 35%. Examples 4 and 5 demonstrate that when the mass fraction of PLA in the film-forming solution is in the range of 11–15 wt%, PLA films with different mechanical properties can be obtained by adjusting the concentration.
[0099] Example 6 A method for preparing polylactic acid films based on a liquid substrate includes the following steps: Step S1: Preparation of polylactic acid (PLA) film-forming solution: Add 1.1g of PLA (using low-melting-point PLA, purity >99%, from Kobin Trading Co., Ltd.) to 8.9g of ethyl acetate (purity >99%, from Macklin), and dissolve by magnetic stirring at 60°C for 45min to obtain PLA film-forming solution. The mass fraction of PLA in the PLA film-forming solution is 11wt%. Step S2: Prepare the liquid substrate: Take a clean glass container and add the aqueous liquid, which is deionized water, into the container to obtain the liquid substrate. The liquid level of the liquid substrate is 4 cm. Perform temperature control treatment on the liquid substrate by placing it in an ice bath to stabilize the water temperature at 0 ℃. Step S3: Use a pipette to draw 1000 μL of polylactic acid film-forming solution, keeping the dispensing end of the pipette in tangential contact with the liquid surface of the liquid substrate, and apply the polylactic acid film-forming solution to the liquid surface of the liquid substrate at a uniform speed. After the polylactic acid film-forming solution contacts the liquid surface of the liquid substrate, it quickly spreads and forms a thin film. The supply rate of the polylactic acid film-forming solution is 2 mL / min. Step S4: After the film formed in step S3 has been left to stand for 2 minutes, the film is collected from the surface of the liquid substrate with tweezers, washed with deionized water 3 times, and dried at 40°C for 20 minutes to obtain a polylactic acid film.
[0100] Example 7 Compared with Example 6, the difference in Example 7 is that the mass fraction of polylactic acid in the polylactic acid film-forming solution is 12 wt%, while the other steps are the same.
[0101] Example 8 Compared with Example 6, the difference in Example 8 is that the mass fraction of polylactic acid in the polylactic acid film-forming solution is 13 wt%, while the other steps are the same.
[0102] Performance testing: The optical properties of the thin film were tested using a UV-Vis spectrophotometer to measure total transmittance and diffuse transmittance, and haze was calculated according to JIS K7136. The surface pore structure of the thin film was characterized by SEM (scanning electron microscopy), and the average pore size, pore size distribution, and pore density were statistically analyzed using ImageJ. The mechanical properties of the thin film were tested using a universal tensile testing machine, and tensile strength and elongation at break were tested according to GB / T 1040.3-2006. The preservation performance of fruits and vegetables was evaluated through a red grape wrapping experiment, with the area of wrinkled appearance and moisture loss as indicators.
[0103] 1. Film formation feasibility test: This invention utilizes a polylactic acid film-forming solution (polylactic acid-ethyl acetate solution) to perform liquid-liquid interfacial superspreading film formation on the surface of an aqueous liquid substrate. For example... Figure 2 As shown, in Examples 6, 7, and 8, under the conditions of a 0°C aqueous liquid substrate and a polylactic acid (PLA) film-forming solution with a volume of 1000 μL, PLA film-forming solutions with concentrations of 11 wt%, 12 wt%, and 13 wt% all rapidly spread on the water surface and formed continuous films. Figure 3 As shown, in Examples 1, 2 and 3, a 13 wt% polylactic acid film-forming solution was rapidly spread and formed a continuous film on an aqueous liquid substrate at 0 ℃, 25 ℃ and 35 ℃ under the condition that the volume of the polylactic acid film-forming solution was 800 μL.
[0104] 2. Characterization of Janus' asymmetric structure: The polylactic acid film prepared by this invention can form an asymmetric Janus film with different structures on both sides, which is particularly evident on a low-temperature aqueous liquid substrate. Figure 4 SEM images (both at 5.0 kV, 25 mA, gold sputtering for 90 s) of the polylactic acid films from Examples 8, 4, 5, 6, and 7 are shown. (From...) Figure 4 It was observed that in samples with an aqueous liquid substrate at 0 °C, a high-density micropore structure formed on the side near the water, while the other side was relatively dense. The pore size, pore density, or pore area ratio differed on the two sides, thus forming an asymmetric Janus structure.
[0105] 3. Characterization of temperature-controlled thin film structure and optical properties: Examples 1, 2, and 3 demonstrate that films prepared from polylactic acid (PLA) film-forming solutions of the same PLA concentration at different liquid substrate temperatures exhibit significant differences in haze. Figure 5 Macroscopic haze test diagrams for Examples 1 and 2 are shown. Figure 6The transmittance and haze spectra of the polylactic acid films from Examples 1, 2, and 3 are shown, as follows: Figure 5 , Figure 6 As shown in Table 1: The polylactic acid (PLA) film in Example 1 exhibits different total transmittance and diffuse transmittance on the air and water sides, with haze values of 84.10% and 83.85%, respectively. It should be noted that the increased porosity on the water side of the PLA film does not necessarily lead to a higher haze value measured from the water side. This is because the measured haze is not the surface porosity of a single side, but rather the total scattering result after light passes through the entire film. The difference in transmittance between the water and air sides in Example 1 demonstrates different structures on both sides. However, since both air and water side incidence passes through the same porous scattering layer, the macroscopic haze values measured from both sides are similar. During water side incidence, the porous structure may cause more interface reflection, backscattering, or light loss, reducing both total and diffuse transmittance. During air side incidence, light first enters the relatively dense layer before reaching the porous water side layer, making some scattering more easily collected by the integrating sphere in the form of transmission scattering. Therefore, even with more porosity on the water side, the haze value during water side incidence is not necessarily higher.
[0106] When prepared on liquid substrates at 25°C and 35°C (corresponding to Examples 2 and 3, respectively), the haze on the air and water sides was consistent, with the polylactic acid films of Examples 2 and 3 having haze of only 6.12% and 5.55%, respectively. Meanwhile, the total transmittance of the polylactic acid films of Examples 2 and 3 were 93.28% and 93.05%, respectively, exhibiting high transparency and low haze.
[0107] Macroscopic changes in haze of thin films are related to their microporous structure at the microscopic level. Figure 7 Optical microscope images of the polylactic acid films of Examples 1, 2, and 3 on the air and water sides are shown. Figure 8 SEM images of the polylactic acid films on the air and water sides of Examples 1, 2 and 3 are shown (all sputtered with gold at 5.0 kV, 25 mA for 90 s). Figure 9 The diagram shows the pore size distribution of the polylactic acid (PLA) film on the water side of Example 1. The PLA film prepared on a liquid substrate at 0 °C has uniform micropores on its surface. The average pore size of the PLA film on the water side of Example 1 is about 1.9 μm, and the pore size is concentrated in the range of 1.5 to 2 μm.
[0108] Table 1. Mean total reflectance and diffuse reflectance of polylactic acid (PLA) films with a PLA concentration of 13 wt% at different liquid substrate temperatures, as well as the mean calculated haze data.
[0109] 4. Mechanical property testing: The polylactic acid films obtained in Examples 8, 4, and 5 were tested for tensile strength and elongation at break, as follows: Figure 10 As shown in Table 2, the tensile strength of the obtained polylactic acid film can reach about 15 to 29 MPa, and the elongation at break can reach about 21% to 38%, indicating that the polylactic acid film has basic mechanical properties that are transferable, can be coated, and can be tested for subsequent applications.
[0110] Table 2. Tensile strength and elongation at break test results of polylactic acid films from Examples 8, 4, and 5. 5. Freshness preservation performance test: The polylactic acid (PLA) film prepared by the method in Example 2 was used for testing. This film exhibits high transparency and good film-forming integrity, facilitating observation of changes in fruit appearance and verifying the feasibility of using the PLA film of this invention as a biodegradable food packaging film. Clean red grapes without obvious mechanical damage were wrapped with the PLA film prepared by the method in Example 2. Unwrapped red grapes were used as a blank control. The fruits were placed and observed under the same conditions. The testing procedures are as follows: (1) Sample pretreatment: Select two purple red grapes with good surface cleanliness (no obvious color change or mechanical damage) and plump shape, wash them with deionized water and place them in a sterile petri dish for later use. (2) Thin film preparation: Using the method of Example 2, a uniform PLA thin film was prepared on the surface of deionized water and left to stand until the solvent completely evaporated to form a stable film structure; (3) Sample wrapping: The pretreated red grapes are gently placed on the surface of the cured film. The film-fruit contact is achieved through interfacial tension. Then, sterile tweezers are used to completely wrap the fruit in the PLA film. During the operation, the surface of the film is strictly controlled to prevent water from flowing into the film. (4) Control setting: Take an equal weight of untreated red grapes as a blank control and place them together with the coated sample in a constant temperature and humidity environment (25±1 ℃, RH 60±5 %) for 18 days to observe the process of water loss and putrefaction.
[0111] like Figure 11As shown, the experimental control group (left red grapes) and the plastic wrap-treated group of Example 2 (right red grapes) showed significant differences: due to the lack of surface water retention measures, the control group showed micro-wrinkling of the skin on the 4th day, and by the 9th day, significant shrinkage had formed; while the treated group did not show obvious morphological changes during this period. Continued observation until the 13th day showed that the wrinkling degree of the control group continued to deepen, while the treated group maintained good morphological stability. Experimental data on the 18th day showed that the skin wrinkling area of the control group reached 98.7% ± 1.2%, while the treated group, after unpacking, showed only slight wrinkling in local areas (wrinkled area ≤ 20.0% ± 3.1%), and its overall morphological integrity was significantly better than the control group (p < 0.01). Compared with the unwrapped blank control group, the water loss rate of red grapes wrapped with polylactic acid film was reduced by approximately 78.7%. This result confirms that the polylactic acid film prepared according to this invention can effectively delay the morphological deterioration caused by post-harvest water loss of red grapes, and is suitable for biodegradable preservation packaging of fresh agricultural products such as fruits and vegetables.
[0112] 6. XRD (X-ray diffraction) and DSC (differential scanning calorimetry) characterization: like Figure 12 As shown, both films in Example 1 and Example 2 have broad signal peaks around 15.6 °, and the peak differences are small. This proves that the crystallinity of the room temperature sample and the ice water sample is low, the amorphous region accounts for a large proportion, which leads to the broadening of the diffraction peaks, and the difference in crystallinity is small, with no very obvious difference in crystallinity.
[0113] like Figure 13 As shown, the samples formed at low temperature and room temperature exhibit a difference of approximately 3 °C in the DSC melting endothermic peak, mainly due to minor changes in the arrangement of molecular chains and crystallinity during film formation. This difference reflects the regulatory effect of film formation temperature on the microstructure of the material. However, since the PLA material used itself has low crystallinity, the difference in crystallinity is small and has no significant impact on haze or other properties.
[0114] Comprehensive analysis shows that the DSC thermal analysis results are consistent with the XRD characterization data, confirming that the haze differences among PLA film samples are not due to changes in material crystallinity. The mechanism by which crystallinity affects the haze differences of PLA film samples has been clearly ruled out. Therefore, the most direct influence on the haze of polylactic acid films is due to differences in micropores in the microstructure, and is unrelated to the degree of polymer crystallinity.
[0115] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing polylactic acid thin films based on a liquid substrate, characterized in that, Includes the following steps: Step S1: Prepare polylactic acid film-forming solution: Add polylactic acid to ethyl acetate and stir to dissolve, thus obtaining polylactic acid film-forming solution; Step S2: Prepare the liquid substrate: Add the aqueous liquid to a container to obtain the liquid substrate, and perform temperature control treatment on the liquid substrate; Step S3: Add the polylactic acid film-forming solution into the injection tool, so that the liquid outlet of the injection tool contacts the liquid surface of the liquid substrate, so as to apply the polylactic acid film-forming solution to the liquid surface of the liquid substrate. After the polylactic acid film-forming solution contacts the liquid surface of the liquid substrate, it spreads on the liquid surface to form a thin film. Step S4: After the film formed in step S3 has been allowed to stand, the film is collected from the surface of the liquid substrate and dried to obtain a polylactic acid film. The temperature of the liquid substrate is adjusted to regulate the pore structure and haze of the polylactic acid film.
2. The method for preparing polylactic acid films based on a liquid substrate according to claim 1, characterized in that, The temperature of the liquid substrate is 0–50°C.
3. The method for preparing polylactic acid films based on a liquid substrate according to claim 1, characterized in that, In step S1, the polylactic acid is selected from one or more of low-melting-point polylactic acid, high-melting-point polylactic acid, polylactic acid homopolymer, polylactic acid copolymer and modified polylactic acid; The polylactic acid film-forming solution contains 5–20 wt% polylactic acid.
4. The method for preparing polylactic acid films based on a liquid substrate according to claim 1, characterized in that, The polylactic acid film-forming solution contains 11-15 wt% polylactic acid.
5. The method for preparing polylactic acid films based on a liquid substrate according to claim 1, characterized in that, The aqueous phase liquid is water or deionized water; The liquid level of the liquid substrate is 2 to 8 cm.
6. The method for preparing polylactic acid films based on a liquid substrate according to claim 1, characterized in that, In step S3, the applied volume of the polylactic acid film-forming solution is 15 μL to 20 mL, and the supply rate of the polylactic acid film-forming solution is 0.1 to 10 mL / min.
7. The method for preparing polylactic acid films based on a liquid substrate according to claim 1, characterized in that, In step S4, the film is left to stand for 0.5 to 30 minutes, and is dried at 30 to 50 °C for 10 to 60 minutes.
8. The method for preparing polylactic acid films based on a liquid substrate according to claim 1, characterized in that, The polylactic acid film obtained after drying in step S4 has a thickness of 0.05–100 μm and a haze of 3–95%.
9. A polylactic acid film, characterized in that, It was prepared using the method for preparing polylactic acid films based on a liquid substrate as described in any one of claims 1 to 8.
10. The application of polylactic acid film as described in claim 9 in food packaging.